A Ética e deontologia aplicada a profissionais de contabilidade: análise do comportamento do profissional de contabilidade em tempos de pandemia - Soares, Edite Cristina Moreira (2019)
In a world in which it is increasingly able to keep up with changes and which, at the same time, needs more ethical values, accounting professionals play a fundamental role in helping and finding solutions for those who contact them. The objective of this dissertation is to analyze the relevance and impact of the CC code of ethics and deontology in the activity of certified accountants and, through a case study, analyze the importance of professional ethics and deontology in accounting, the most important principles to be considered and how accountants in the face of pandemic situations behaved ethically. Thus, it is relevant to make a theoretical framework given the relevance of ethics, especially in the accounting profession, and how it takes into account ethical standards and deontological principles in carrying out their functions. As for the methodology to be used, a questionnaire was sent to 102 CC registered at the OCC, with only 53 responses being obtained. However, the data obtained allowed to demonstrate that the CC is a fundamental professional in the economic and financial health of a given company, especially in times of pandemic, supporting it in the fight against bankruptcy, never forgetting ethical principles. With this, given the data presented, it was possible to draw two conclusions. The first is that certified accountants attach great importance and use to the code of ethics and deontology and the second is that the CC, despite the difficulties they encountered, from increased work, increased pressure, less rest time, more responsibilities, were able to be the main support of companies, in the analysis of economic and financial health, helping them to fight bankruptcy An important aspect to bear in mind refers to the role that accountants play in society and with the companies to which they provide services. Since this is a profession in constant change, the accounting professional must adopt a dynamic and innovative profile, looking for updates as a way to enrich their professional activity. In short, given the studied review and analyzed data, it was possible to respond to the study objective. Given that it focused on the analysis and importance of the code of ethics and deontology in the activity of certified accountants, in addition to having removed the information in a clear and objective manner, we were able to reconcile two points, namely, the importance of ethics and deontology in the CC profession and its influence on CC behavior in times of pandemic.